2013
DOI: 10.3389/fncom.2013.00108
|View full text |Cite
|
Sign up to set email alerts
|

Direct connections assist neurons to detect correlation in small amplitude noises

Abstract: We address a question on the effect of common stochastic inputs on the correlation of the spike trains of two neurons when they are coupled through direct connections. We show that the change in the correlation of small amplitude stochastic inputs can be better detected when the neurons are connected by direct excitatory couplings. Depending on whether intrinsic firing rate of the neurons is identical or slightly different, symmetric or asymmetric connections can increase the sensitivity of the system to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In all the systems considered here, the oscillators have similar natural frequency, and the connections are of similar coupling strength and time delay in transmission of pulse to other oscillators. It was previously shown that for any identical pair of symmetrically coupled oscillators with delayed couplings, the stability of inphase or anti-phase state depends on the delay and slope of the coupling function [6,27,65,66]. With the sinusoidal coupling used here, we chose time delay between T /2 and 3T /2, where T is the period of the oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…In all the systems considered here, the oscillators have similar natural frequency, and the connections are of similar coupling strength and time delay in transmission of pulse to other oscillators. It was previously shown that for any identical pair of symmetrically coupled oscillators with delayed couplings, the stability of inphase or anti-phase state depends on the delay and slope of the coupling function [6,27,65,66]. With the sinusoidal coupling used here, we chose time delay between T /2 and 3T /2, where T is the period of the oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…In the classical models of synchronization, collective state of a system of coupled oscillators is determined by the outcome of rivalry between synchronizing effect of connections and desynchronizing effect of inhomogeneity 2 , but there are examples of the systems in which synchrony is enhanced by inhomogeneity 38 39 40 41 . Recently we have shown that small inhomogeneity can increase correlation between spike trains of two coupled neurons 42 . In this study we develope a framework for the correlation of weakly coupled phase oscillators with a given phase sensitivity when they are driven by small amplitude noises.…”
mentioning
confidence: 99%
“…In the classical models of synchronization, collective state of a system of coupled oscillators is determined by outcome of rivalry between synchronizing effect of connections and desynchronizing effect of inhomogeneity [ 2 ]. Yet there are examples of the systems in which inhomogeneity enhances synchrony [ 3 , 4 ]. In this study we have developed a general framework for the correlation of coupled neuronal oscillators with a given phase sensitivity and we have shown that in some cases, for identical neurons, synchronized state is an unstable attractor and arbitrarily weak noise can destroy synchrony.…”
mentioning
confidence: 99%